Study the Philosophy of Islamic Law in Determination Percentage of Zakat Mal - Muhamad Ulul Albab Musaffa; Dakum Dakum; Ahmad Hujaj Nurrohim; Muhammad Rosyad Sudrajad (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2022)
Abstract: The issue of zakat in today's society is very complex and dynamic. Zakat, which is expected to be an instrument of economic empowerment of the people, must be able to explore its potential. One of the potentials of zakat that can be hope in the development of the Islamic economy is the determination of the percentage of zakat dynamically. This is interesting because the percentage of zakat is considered by some academics to be a fixed thing (tsubut) and cannot be changed, but is that true? And how is the actual determination of the percentage of zakat at the time of the prophet by looking at the socio-historical at that time? Then how is the percentage of zakat contextualized in the current era? This article is a normative-philosophical study, and it is library research using an Islamic legal philosophy approach to the percentage of zakat in this modern era. The result of this article is that the percentage of zakat is not standard (tsubut). Several narrations have implications for scholars' opinion that the percentage of zakat is seen from the masaqah in getting it and is evidence that zakat is dynamic. This is following al-Qarafi's opinion, namely by positioning the prophet Muhammad when setting the zakat percentage policy, not as a messenger of God but rather as a leader in regulating the policies of his people.Abstrak: Isu zakat dalam masyarakat saat ini sangat kompleks dan dinamis. Zakat yang diharapkan menjadi instrumen pemberdayaan ekonomi umat harus mampu menggali potensinya. Salah satu potensi zakat yang dapat diharapkan dalam pengembangan ekonomi Islam adalah penentuan persentase zakat secara dinamis. Hal ini menarik karena persentase zakat dianggap oleh sebagian akademisi sebagai hal yang tetap (tsubut) dan tidak dapat diubah, namun apakah itu benar? Dan bagaimana sebenarnya penentuan persentase zakat pada masa nabi dengan melihat sosio-historis pada saat itu? Lalu bagaimana konteks persentase zakat di era saat ini? Artikel ini merupakan kajian normatif-filosofis, dan merupakan penelitian kepustakaan dengan menggunakan pendekatan filsafat hukum Islam terhadap persentase zakat di era modern ini. Hasil dari pasal ini adalah prosentase zakat tidak baku (tsubut). Beberapa riwayat berimplikasi pada pendapat ulama bahwa persentase zakat dilihat dari masaqah yang mendapatkannya dan merupakan bukti bahwa zakat itu dinamis. Hal ini sesuai dengan pendapat al-Qarafi, yaitu dengan memposisikan Nabi Muhammad SAW dalam menetapkan kebijakan persentase zakat, bukan sebagai utusan Allah melainkan sebagai pemimpin dalam mengatur kebijakan umatnya.